Modern Requirements for Future Professionals in The Field of Journalism - Kahhorova Ugiloy Norchaevna (Genius Journals, 2022)
There are currently no manuals or books on identifying new technologies in journalism in Uzbekistan, although they are in short supply. The purpose of writing the article is to analyse the requirements for young people who are conducting research in this field and are just entering the field of journalism, using new methods.
Keywords: SMM in Journalism; PR; students in Uzbekistan; people